PERMASALAHAN KEBISINGAN DI KOTA DENPASAR - I W. Suarna; C.I.P. Kusuma K.; I M. Sara Wijana (Environmental Research Center (PPLH) of Udayana University)
Research on the condition of air pollution in Denpasar City was carried out inthe mid of 2007. Aims of this activity was to find out noise levels which occured ondifferent sites with different uses, so the solution for the problems can be found out andthe impact can be minimised.Data on noise levels were measured by using sound level metres, while samplingsites were determined by GPS, so replication can be exactly made on the same samplinglocations. Fivty measurements were made on the sites where impacts of noiseencountered by activities surrounding them.Results of the study showed that on the schools, settlements, and open-green areathe noise levels have exceeded the benchmarks. As a result, some efforts need to becarried out , such as improvements of roads, and planting more trees which were not onlyused to minimized noise levels but also can improve aestetic levels of the city.